Variation of DNA Repair System Genes (XRCC1) rs25487 and (RAD18) rs373572 in Methamphetamine Abuse Cases - Shaimaa A. Al-Oubaidy; Mazin Eidan Hadi; Sura A. Awadh (Medical Journal of Babylon)
Background: Methamphetamine abuse has significantly increased among the young Iraqi population in the past year. Objectives: The current study aimed to detect variations in the X-ray repair cross-complementing protein 1 (XRCC1) rs25487 and E3 ubiquitin-protein ligase (RAD18) rs373572 genes in cases of addiction. Materials and Methods: Blood samples and data collection: 1 mL of the whole blood sample was collected from each patient who attended the Psychiatric Center, Marjan Teaching Hospital, Hillah, Babylon Governorate, from February 2023 to May 2023. Then, the blood samples were transferred to the lab for deoxyribonucleic acid extraction and target sequence amplification. Results: The results indicated that the XRCC1 genotyping distribution for AG was observed more, with the case group, than in the control group, and the GG genotype was found less in the case group than the control group, with significant differences [odds ratio (OR) = 4.649, P = 0.0219)]. The AA genotyping was not observed in the case group, but was found to a minimal extent in the control group with nonsignificant differences (OR = 0.4286, P = 0.598); the allele A was strongly associated with Meth in the case samples, demonstrating significant differences. The genotyping of the RAD18 gene showed the Gln/Arg genotype was highly frequent in both cases and the control group, whereas Gln/Gln was more frequent in the case group compared with the control, with significant differences (OR = 8.400, P = 0.0118). The Arg/Arg genotype was not observed in the healthy control group with nonsignificant differences (OR = 12.87, P = 0.098). The allele frequency showed a non-significant distribution (OR = 1.060, P = 0.835). Conclusion: From these results, we can conclude that there were strong associations between XRCC1 and RAD18 and Meth addiction in the cases studied.